해수 암모늄 자료의 재평가: 독특한 단주기 수질지표 가능성 - 정용훈; 양재삼; JEONG, YONG HOON; YANG, JAE SAM (Pada (Hanʼguk Haeyang Hakhoe), 2016)
We have evaluated the ammonium data in seawater as a potential short-term index for marine environment through the following steps. 1. reviewing of chemical characteristics of ammonium in seawater, 2. comparative relationships of ammonium data with other water quality indices such as DO, COD, and nutrients from Typical Marine Environment(TME) and Special Marine Environment(SME). Ammonium data generally represent negative correlation with DO, while positive correlation with COD. In particular, under frequent cases of seawater conditions showing similar concentration of COD or DO, we have limited choice of explanation for such situation. However ODIN(ODIN/RDIN) or RDIN(RDIN/TDIN) ratio could provide advanced information to understand these seawater conditions. Based on these results, we suggest ammonium data as a potential short-period index for transilient marine environment, such as benthic flux of bottom sediment, hypoxia, and algal bloom. Under overcoming several handicaps, ammonium data could be an useful tool for better understand short transformation of marine environment. 해수 내 용존 암모늄이온의 농도 자료가 해양환경의 지표로서 가치가 있는지 평가하였다. 먼저 암모니아의 화학적인 특성을 정리하였고, 본론에서 해양환경의 대표성을 띠는 일반해역(원양, 연안, 자연하구역)과 집중비교해역(골재채취해역, 하구역)에서 암모늄 자료의 가치를 비교하였다. 암모늄은 일반해역에서 전반적으로 DO와 음의 상관관계를 갖고, COD와 양의 상관관계를 보임으로써 수질지표로서 광범위한 적용 가능성을 보였다. 특히 DO 또는 COD가 유사한 농도를 나타내는 해양환경조건의 경우, 보다 상세한 해석이 불가능하였으나 ODIN 비율 (산화성용존무기질소: ODIN/TDIN ratio) 혹은 RDIN 비율 (환원성용존무기질소: RDIN/TDIN ratio)를 적용하면, 비교대상 해역의 산화 및 환원 조건에 대한 보다 향상된 정보를 얻을 수 있었다. 집중비교해역에서는 저층퇴적물의 확산, 식물플랑크톤의 단기변화 등 주로 단주기 환경변화와 관련하여 암모늄의 지표로서 잠재력을 확인하였다. 암모늄은 기존의 몇 가지 단점을 보완한다면 해양환경에서 단주기로 변화하는 해양한경을 이해하는데 도움이 될 것으로 판단된다.